Lahirnya Intelegensia di Aceh dan Posisinya dalam Kontestasi Formasi Sosial Pasca Formalisasi Agama - Miswari; Miswari, Miswari (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2023)
This article aims to analyze the emergence of intellectual movements in Aceh after the occurrence of Dutch colonialism and the start of modernization. As with the phenomena that emerged in the Dutch East Indies in general, the presence of the Dutch in Aceh caused traditional intellectual movements based in Islamic boarding schools to respond to modern public schools which were indicated to carry the spirit of secularism which was considered to endanger the identity of the Acehnese people. The responses that emerged were resistance, negotiation, and accommodation. The research method of this article uses a historical approach based on literature review. The author conducted a review of the literature related to research. The collected data is verified, analyzed, and reconstructed narratively. The research findings show that the intellectual group is divided into three variants, namely the resistant group, namely the traditional intellectual party based on Islamic boarding school education, the negotiative group, namely the modernist intellectual party based on madrasah education, and the accommodative group, namely the secular party based on school education. These three intellectual variants continue to play their role in the formation of social formations in Aceh. After the conflict, due to pressure from social formations, between dayah groups, madrasahs and schools, there was a contestation for dominance. As a result, modernist groups win over discourses and ideas, traditional groups become fighters for modernist ideas and discourse, and secular groups follow the wishes of traditional groups.